Web and wireless geographical information systems 10th international symposium, W2GIS 2011, Kyoto, Japan, March 3-4, 2011 : proceedings - W2GIS (Symposium) Kyoto, Japan) 2011; Tanaka, Katsumi; Fröhlich, Pete; Kim, Kyoung-Soo; SpringerLink (Online service)e. (Berlin New York Springer, 2011)
This book constitutes the refereed proceedings of the 10th International Symposium on Web and Wireless Geographical Information Systems, W2GIS 2011, held in Kyoto, Japan, in March 2011. A total of 13 full and 3 short papers plus 2 short keynote papers presented were carefully reviewed and selected from 36 submissions. The papers cover a wide range of topics including geographic information retrieval on the web, geo-spatial semantic and sensor web, location-based services, advanced GIS visualization techniques, personalization and adjustment for mobile GIS applications, and geo-spatial data quality and context processing.
Electronic reproduction.
Keywords: Geographic information systems -- Congresses; Wireless communication systems -- Congresses; Electronic books